2014
DOI: 10.1038/srep07450
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of CO poisoning on Pt catalyst coupled with the reduction of toxic hexavalent chromium in a dual-functional fuel cell

Abstract: We propose a method to enhance the fuel cell efficiency with the simultaneous removal of toxic heavy metal ions. Carbon monoxide (CO), an intermediate of methanol oxidation that is primarily responsible for Pt catalyst deactivation, can be used as an in-situ reducing agent for hexavalent chromium (Cr (VI)) with reactivating the CO-poisoned Pt catalyst. Using electro-oxidation measurements, the oxidation of adsorbed CO molecules coupled with the concurrent conversion of Cr (VI) to Cr (III) was confirmed. This c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
45
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(46 citation statements)
references
References 40 publications
0
45
0
1
Order By: Relevance
“…CO electro-oxidation is important for both proton-exchange membrane fuel cells [1][2][3] and direct methanol fuel cells [4,5]. Due to its importance, CO electro-oxidation has been extensively studied for many years.…”
Section: Introductionmentioning
confidence: 99%
“…CO electro-oxidation is important for both proton-exchange membrane fuel cells [1][2][3] and direct methanol fuel cells [4,5]. Due to its importance, CO electro-oxidation has been extensively studied for many years.…”
Section: Introductionmentioning
confidence: 99%
“…Deactivation of the catalysts can also be a cause of different reaction rates which can be caused by: (1) Pt deactivation due to CO poisoning caused by excess CO in the feed which blocks the sites for H2O dissociation [92,97], (2) sintering of Pt to form large clusters [98], (3) formation of highly stable carbonates over the Pt-ceria active sites on the catalyst [99], thereby rendering them unavailable, (4) growth in the crystallite size of ceria under extended operation at high temperature which compromises its reducibility [93], (5) loss of faceted surface of ceria [100] and (6) reduction of the Pt dispersion on ceria [101]. From the BET surface area analysis we found that the surface area of the catalysts reduced by 38% (C1/Pt), 75% (C2/Pt) and 44% (C3/Pt) after 100 hours of operation.…”
mentioning
confidence: 99%
“…Nonetheless, one must bear in mind that variations in the efficiency of the process can occur because of the production of carbon monoxide and carbon dioxide during the electrolysis of methanol as carbon monoxide may react with the platinum catalyst, thus deactivating the anode. Research efforts on how to counteract this effect have been undertaken in the past few years [28]. On the other hand, the carbon dioxide can incur in further operating costs or be collected for utilization.…”
Section: Resultsmentioning
confidence: 99%